أثر فطريات معززة النمو النبات على نمو نبات الفول - خته, رميصاء; زينب, طبال; كريمة, طرية (University of Eloued جامعة الوادي, 2022)
Microorganisms, including environmental foundation fungus are healthy and productive, affecting physiological qualities for many. This research experiments were conducted in the Wadi Rig area in the state of Mughayr during the academic year 2021-2022 With a view to studying the impact of the fungi enhanced for the growth of the local plant Vicia faba L. The experiment is designed to choose 80 plastic pots divided into four groups with specific agricultural terms each group containing 20 pots, and each group is divided into two sections of a section containing samples and the second section containing the samples that have been treated with fungi during the vegetable phase of bean plant. The results obtained that the fungi has affected the classrooms for the vegetable plant once positive and other with no sense . - The treatment of fungi has also affected the increased content of chlorophyll and dissolute and carotene sugars , but we have a declined in the content of proline compared to the control.
التنوع الحيوي و المحيط
Keywords: bean plant; Vicia faba L; Mycorhiza; improvement.; نبات الفول ، الميكوريزا ، الإنبات